Formuły dziewiętnastowiecznych akt chrztu na przykładzie ksiąg metrykalnych warszawskiej parafii św. Jana Chrzciciela = 19th-century acts baptism formulas based on the example of register books of the St. John`s parish in Warsaw - Żurek, Aleksandra (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The aim of the article is to introduce the 19th-century formulas of the acts of baptism based on the example of register books of St. John`s parish in Warsaw from the years 1826-1867. After a brief introduction of the history of register books and the Polish Kingom`s applicable laws and regulations, the author presents the ways in which acts of baptism were written both in usual and unusual circumstances, for instance when the father of a child was unknown, or when baptism of an adult individual was performed.
Keywords: antroponimia; akta metrykalne; chrzest; Warszawa; prawo; 19 w.; anthroponomastics; parish registers; baptisms; Warsaw; 19th century; law